IBM XIV storage system architecture and implementation - Dufrasne, Betrand; Burns, Christian; Kalabza, Wenzel; Lengyel, Sandor; Schill, Patrick; Schoessler, Christian; Solewin, Stephen (IBM Corporation, International Technical Support Organization, 2014)
"The focus of this edition is on the XIV Gen3 running Version 11.5.x of the XIV system software, which brings enhanced value for the XIV Storage System in cloud environments. It offers multitenancy support, VMware vCloud Suite integration, more discrete performance classes, and RESTful API enhancements that expand cloud automation integration. Version 11.5 introduces support for three-site mirroring to provide high availability and disaster recovery. It also enables capacity planning through the Hyper-Scale Manager, mobile push notifications for real-time alerts, and enhanced security. Version 11.5.1 supports 6TB drives and VMware vSphere Virtual Volumes (VVOL)."--
Includes bibliographical references. - Online resource; title from covers (Safari, viewed December 4, 2014)
Keywords: Storage area networks (Computer networks); Database management; Réseaux de stockage (Informatique); Bases de données; Gestion